Between-seasons variability of cyclists` peak performance: A longitudinal analysis of "real-world" power output data in male professional cyclists - Valenzuela, P. L.; Mateo-March, M.; Muriel, X.; Zabala, M.; Lucia, A.; Barranco-Gil, D.; Pallares, J. G. (International Journal of Sports Physiology and Performance, 2023)
Purpose: The record power profile (RPP) has gained popularity as a method of monitoring endurance cycling performance. However, the expected variation of cyclists` performance between seasons remains unknown. We aimed to assess the between-seasons variability of peak performance (assessed through the RPP) in male professional cyclists.